Aṣe Zärʾa Yaʿǝqobs Kinder: Spuren der Vorbevölkerung von Sǝlṭe-Land - Bustorf, Dirk (Aethiopica, 2006)
The article compiles and analyses those historical narratives collected among the Sǝlṭe of southern-central Ethiopia, which deal with the migration of the later Sǝlṭe and their encounter with the original inhabitants of their new homeland. It correlates newly collected oral traditions (genealogies, local clan histories) and already published oral accounts with written sources. After a definition of the Sǝlṭe and their sub-units, the different traditional concepts of the original inhabitants (e.g., Žära, hagär säb, yafär säb, King Dawe) and the metamorphosis of these concepts are discussed. The claimed descent from aṣe Zärʾa Yaʿǝqob is identified as the dominant idea. The article points out how migration narratives and traditions on the establishment of the relations between original inhabitants and newcomers lay ideological fundaments of territorial claims as well as of identity, which still today are highly relevant.